ELKATU: Pembuatan Pelet Ikan Bandeng Tinggi Protein Berbasis Limbah Bekatul di Desa Gadingsari - Permadi, Adi; Sholihah, Laila Melati Nur; Purwanti, Purwanti; Oemardy, Zalfadhia Luthfia; Khasanah, Fitri Nur; Putri, Aninda Cahaya; Prastiwi, Salma Maulidya; Azizah, Siti Nur; Rosyidah, Ummy; Fadilah, Haqi Miftah; Yanti, Dinda Putri Dwi; Azhar, Sella Angelina; Satria, Rizky Adi; Irawan, Ichsanul Fikri Umar; Ramadhan, Iqbal; Mariska, Novia; Ma’arif, Sandhy Aulia (Pelita: Jurnal Pengabdian kepada Masyarakat, 2024)
The production of rice bran waste pellets was carried out in Gadingsari Village, Kapanewon Sanden, Bantul Regency, Special Region of Yogyakarta. The problem that occurs is that the high price of fish pellets can make it difficult for fish farmers. It is necessary to make fish pellets independently from rice bran waste using raw materials including rice bran, fish meal, corn flour, tapioca flour, vitamins, yeast, molasses or molasses, EM4, and water. The aim is to reduce production costs for fish cultivation by utilizing unused raw materials, such as rice bran. The method used is direct socialization and training. The steps for making fish pellets start from weighing the ingredients, making adhesive, mixing the ingredients, fermenting the ingredients, molding the fish pellets, ovening the fish pellets, and packaging the fish pellets. The resulting fish pellets contain 40% protein.